2022
DOI: 10.1021/acs.cgd.2c00446
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motion and Ligand Stacking Influence Thermal Expansion Behavior and Argentophilic Forces in Silver Coordination Complexes

Abstract: We designed a series of metal–organic solids using ligands with similar molecular structures that were expected to afford coordination complexes with similar solid-state structures. The metal component is silver­(I) p-toluenesulfonate, and the ligands differ in their ability to undergo dynamic molecular motion. Although the ligands are similar in their molecular structure, the metal complexes exhibit different solid-state structures because of differences in π-stacking arrangements and the presence or lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Previous studies have reported molecules containing groups that undergo molecular pedal motion , can disrupt the interactions along the π stack and lead to changes in the thermomechanical properties. In an effort to exploit this, the current study was extended to include the ditopic HaB acceptors with topologies similar to those of BPA: BPE, Azo, and Cl-Azo (Figure ). The cocrystals of these three bipyridines with 1 yield structures that are analogous to 1 ·BPA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported molecules containing groups that undergo molecular pedal motion , can disrupt the interactions along the π stack and lead to changes in the thermomechanical properties. In an effort to exploit this, the current study was extended to include the ditopic HaB acceptors with topologies similar to those of BPA: BPE, Azo, and Cl-Azo (Figure ). The cocrystals of these three bipyridines with 1 yield structures that are analogous to 1 ·BPA.…”
Section: Resultsmentioning
confidence: 99%
“…21 Recently, we reported the roles of molecular pedal motion and ligand stacking on the TE parameters for a series of related silver(I) coordination complexes. 22 In these discrete-based assemblies, ligands πstacked in an edge-to-face or face-to-face geometry and polymorphic behavior was also observed. We determined that the combination of pedal motion and edge-to-face stacking of the aromatic rings resulted in the largest TE within these silver-based solids.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, we have reported that motion-capable functional groups such as the azo (NN) or ethylene (CC) will yield larger TE tensors along the direction in the solid where this motion happens if the group undergoes solid-state pedal motion. , Moreover, the tensors are larger in solids that undergo motion when compared to those containing a rigid group, such as acetylene (CC), which is not capable of pedal motion . Recently, we reported the roles of molecular pedal motion and ligand stacking on the TE parameters for a series of related silver­(I) coordination complexes . In these discrete-based assemblies, ligands π-stacked in an edge-to-face or face-to-face geometry and polymorphic behavior was also observed.…”
Section: Introductionmentioning
confidence: 99%
“…The structural self-assembly is governed by many factors such as metal ions, ligands, reaction temperature, counterions, solvents, and pH of the reaction. [7][8][9][10][11][12] The parameters that are most important for the magnetic property are the bridging ligand and the paramagnetic metal center. Changes in the type of metal center and bridging ligand result in the creation of materials with varying magnetic properties.…”
Section: Introductionmentioning
confidence: 99%